2000
DOI: 10.1007/pl00011821
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of appendicitis and diverticulitis. Part I: Appendicitis

Abstract: CT has become the primary imaging modality for evaluation of possible appendicitis. About 20 % of patients taken to surgery for appendicitis without CT have had a normal appendix removed. CT has demonstrated overall accuracy of between 93 % and 98 %. Alternative diagnoses are seen in 34±80 % of patients without appendicitis but who were suspected of having appendicitis. For evaluation of appendicitis different techniques have been successful, including the use of no contrast, use of oral and intravenous contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…An important advantage of IV contrast is that it allows a complete assessment of other abdominal pathologic conditions [46] . Rhea found that other conditions were diagnosed in 34% to 80% of patients [47] .…”
Section: Discussionmentioning
confidence: 99%
“…An important advantage of IV contrast is that it allows a complete assessment of other abdominal pathologic conditions [46] . Rhea found that other conditions were diagnosed in 34% to 80% of patients [47] .…”
Section: Discussionmentioning
confidence: 99%